LEGAL PROTECTION FOR PARTIES WHO ARE MINUTE TO LOSE IN POST NATURAL DISASTER (TSUNAMI) IN PALU CITY, CENTRAL SULAWESI - Muh. Rizal Yudiansyah Suldani; Akhmad Khisni (Program Studi Magister (S2) Kenotariatan, Fakultas Hukum, Universitas Islam SUltan Agung, 2020)
The formulation of the problems in this study are 1) Legal protection for parties whose minimum deeds are lost after the natural disaster (tsunami) in Palu City, Central Sulawesi, 2) Notary responsibilities for the minimum deeds in the post-natural disaster (tsunami) notary protocol storage in Palu City Central Sulawesi, 3) legal efforts made by a notary against the parties requesting a copy of the missing or damaged certificate of minuta after the natural disaster (tsunami) in Palu City, Central Sulawesi. The research method used in this research is descriptive using an approachsociological empiricalBased on the results of this study, it is known that the legal protection for parties whose actions are lost after the natural disaster (Tsunami) in Palu City, Central Sulawesi is to ensure the rights and obligations of the parties for certainty, order and legal protection for the parties concerned. In making the authentic deed, we must look at the requirements so that it can be said to be an authentic deed. Authentic deeds are made based on law and before public officials. In this case, it starts with the minimum deed making.